(untitled) (Stamford Journal of Pharmaceutical Sciences, 2011)
In the present investigation the n-hexane, carbon tetrachloride and choloroform soluble fractions of crude methanolic extract of Samanea saman bark were tested for antioxidant, antimicrobial and cytotoxic potential. Antioxidant activity of the extracts was evaluated by DPPH radical scavenging assay and total antioxidant activity test. Antimicrobial activity was tested using disc diffusion method against thirteen bacteria and three fungi and cytotoxicity was tested by brine shrimp lethality bioassay. Chloroform and hexane soluble fraction showed IC50 value of 12μg/ml and 14μg/ml respectively in scavenging DPPH radical while the reference Butylated hydroxytoluene showed an IC50 value of 10μg/ml. The carbon tetrachloride fraction showed the highest total antioxidant capacity. The carbon tetrachloride fraction was also found to possess mild to moderate microbial growth inhibitory capacity. In the brine shrimp lethality bioassay, the n-hexane, carbon tetrachloride, chloroform soluble fractions showed LC50 value of 14.94μg/ml, 0.831μg/ml and 3.288μg/ml respectively. The results suggest good antioxidant and cytotoxic potential of chloroform and hexane soluble fractions and antimicrobial activity of carbon tetrachloride fraction of Samanea saman bark extract. Key Words: Samanea saman; Leguminoseae; Cytotoxicity; Antimicrobial; Antioxidant; Total antioxidant capacity. DOI: 10.3329/sjps.v3i1.6792 S. J. Pharm. Sci. 3(1): 11-17